Pengaruh Media Tanam terhadap Karakter Morfologi dan Hasil Bunga Kenop (Gomphrena globosa L.) dari Sibang Gede Kabupaten Badung - Rahayu, Dewa Ayu Putu Sri; Dwiyani, Rindang; Darmawati, Ida Ayu Putri (Agrotrop : Journal on Agriculture Science, 2025)
Effect of Planting Media on Morphological Characters and Yield of Kenop Flower ( Gomphrena globosa L.) from Sibang Gede, Badung Regency . Kenop flower ( Gomphrena globosa L.) or known as Bunga Ratna in Bali is one of the flowers used in religious ceremonies. This flower needs to be planted in an environment that supports its growth and development to achieve the potential of kenop flowers both in terms of morphology and yield. Planting media as a place for roots and nutrient providers is one of the environmental factors that affect plant growth. The use of planting media must be adjusted to the type of plant to be cultivated. Therefore, the purpose of the research is to get the composition of planting media that is suitable for the growth and yield of Kenop Flower. This study used a factorial Randomized Group Design of 2 factors and 3 replications. The first factor is the different phenotypes of purple (Fu), pink (Fm), and white (Fp) of kenop flowers and the second factor is the difference in planting media namely Ma (husk charcoal), Mt (soil), Mta 11 (soil and husk charcoal 1:1), Mta 21 (soil and husk charcoal 2:1), and Mta 12 (soil and husk charcoal 1:2). The results showed that the interaction between phenotypic factors and planting media had no significant effect on morphological characters and yield in kenop flower plants. However, the single factor of phenotype had a significant effect on the variable of early flowering time. The flowering time of the purple phenotype is 80,33 days after planting, significantly different from the flowering time of the white phenotype which is 80,93 days after planting and the pink phenotype at 91.47 days after planting. The single factor of planting media had no significant effect on the morphological characters and yield of kenop flowers. However, Ma media tends to excel in yield variables, while Mta11 media tends to provide higher values on morphological character variables.